The electricity demand of an EV providing power via vehicle-to-home and its potential impact on the grid with different electricity price tariffs. (May 2020) - Aguilar-Dominguez, Donovan; Dunbar, Alan; Brown, Solomon
Abstract: Electricity demand is expected to grow in the upcoming years due to the electrification of transport, which will likely result in an increase in electricity peak demand when charging at home; this would not represent a problem for the electric vehicle (EV) owner but could potentially destabilise the grid. This work has compared the use of stationery and vehicle-to-home (V2H) energy storage systems to minimise the electricity bill for the household consumers. The impact of using different electricity tariffs and the peak demand derived by this was also investigated. Real-world data was used to model the availability of the EVs to provide V2H during the day. Constraints to guarantee adequate charging of the EV to ensure the ability to provide transportation have been implemented. Two different stationary batteries and two EVs were used for the simulations. High peaks on the demand of up to 6 kW per vehicle (the bi-directional charger's maximum capacity) and up to 5 kW (the batteries charger's maximum capacity) are expected every time that the electricity price drops, and low peaks are expected when the electricity price increases. Moreover, high peaks are expected mostly at night when the electricity price tends to be cheaper and/or after driving the EV and plug it again to charge, however the model will try to constraint the charging of the EV until the price is low again unless there is a journey likely to happen in the near future. The combination of PV generation with a stationary battery or a V2H technology can produce savings of at least 30% regardless the electricity tariff and a reduction of up to 85% in the electricity bill can be achieved under the Time-of-day tariff. The results give a perspective of what can the grid expect when charging an EV at home during winter.